Color-Shift Keying and Code-Division Multiple-Access Transmission for RGB-LED Visible Light Communications Using Mobile Phone Camera - Shih-Hao Chen; Chi-Wai Chow (IEEE Photonics Journal, 2014)
Light-emitting diodes (LEDs) have been deployed for various applications in our daily lives. Similarly, image sensors or cameras integrated into mobile phones have become common. Hence, visible light communication (VLC) using LED and mobile phone cameras is attractive and provides low-cost wireless communication. In this paper, we propose and demonstrate a VLC system using color-shift-keying (CSK) modulation and code-division multiple-access (CDMA) technology simultaneously for the first time; a mobile phone camera is used as the receiver (Rx). CSK is used to enhance the VLC system capacity and to mitigate the single color light interference, whereas CDMA allows multiple users to access the network. The system design and operation mechanism of the proposed CSK-CDMA VLC system are discussed. A proof-of-concept demonstration is performed, and error-free transmission is achieved for multiple-access users. A 3-dB transmission gain is also obtained in each user when compared with the traditional on-off keying (OOK) modulation.